2012
DOI: 10.1152/jn.00196.2012
|View full text |Cite
|
Sign up to set email alerts
|

β- And γ-band EEG power predicts illusory auditory continuity perception

Abstract: Because acoustic landscapes are complex and rapidly changing, auditory systems have evolved mechanisms that permit rapid detection of novel sounds, sound source segregation, and perceptual restoration of sounds obscured by noise. Perceptual restoration is particularly important in noisy environments because it allows organisms to track sounds over time even when they are masked. The continuity illusion is a striking example of perceptual restoration with sounds perceived as intact even when parts of them have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Recent EEG and fMRI studies of humans confirm a role for auditory cortex in the perceptual restoration of obscured sounds (Heinrich, Carlyon, Davis, & Johnsrude, 2008, 2011; Micheyl et al, 2003; Riecke, van Opstal, Goebel, & Formisano; Riecke et al, 2009, Riecke et al, 2012; Vinnik, Itskov, & Balaban, 2012). Single-unit recordings from the mammalian auditory cortex in cats (Sugita, 1997; but see Micheyl et al, 2003) and rhesus macaques (Petkov, O'Connor, & Sutter, 2007) have identified neural correlates of auditory induction, consistent with the purported contribution of cortical processing (see also Kubota, Miyamoto, Hosokawa, Sugimoto, & Horikawa, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Recent EEG and fMRI studies of humans confirm a role for auditory cortex in the perceptual restoration of obscured sounds (Heinrich, Carlyon, Davis, & Johnsrude, 2008, 2011; Micheyl et al, 2003; Riecke, van Opstal, Goebel, & Formisano; Riecke et al, 2009, Riecke et al, 2012; Vinnik, Itskov, & Balaban, 2012). Single-unit recordings from the mammalian auditory cortex in cats (Sugita, 1997; but see Micheyl et al, 2003) and rhesus macaques (Petkov, O'Connor, & Sutter, 2007) have identified neural correlates of auditory induction, consistent with the purported contribution of cortical processing (see also Kubota, Miyamoto, Hosokawa, Sugimoto, & Horikawa, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Samuel's paradigm 22 ). Our method subscribes to the latter approach, also referred to as 'filling-in', which emphasizes the signal detection strategy followed in cases where a listener classification is inconsistent with the token absence in a gap 3,[23][24][25][26][27][28][29] . As has been noted 30 , from the listener's utilitarian perspective, this effect of induction in a challenging environment is not aimed at the production of decision errors (or illusions) but to assist against masking.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on stimulus, neural correlates have been localized to different areas, including Heschl's gyrus for missing AM noise 36 , the posterior aspect of superior temporal gyrus for disrupted vowels 28 , and wider brain networks including the superior temporal lobe in the case of missed phonemes 24,37 . In addition, mixed evidence points to a basis for restoration in terms of endogenous modulations to boundary encoding: on the one hand, the search for differential onset responses to noise when under restoration, indexing alternative encoding, has yielded negative results so far 27,28 ; on the other, induced narrow-band (3-4 Hz) desynchronizations that are restoration-specific, and occur after gap onset, have been suggested by results from EEG 28,38 .…”
Section: Cc-by 40 International License Peer-reviewed) Is the Authormentioning
confidence: 99%
See 2 more Smart Citations